Cytogenetic characterization of the murine bladder cancer model MB49 and the derived invasive line MB49-I - Fabris, Victoria Teresa (2012)
Bladder cancer isfrequently associated with chromosomal abnormalities, andthe complexity of karyotypes increases with tumor progression. The murine model MB49 is one of the most widely studied models of bladder cancer.We developed the invasive cell line MB49-I by successive in vivo passages of MB49 primary tumors. Because little is known about the chromosomal alterations of this model, our goal was to perform cytogenetic analyses of the MB49 and MB49-I lines. The karyotypes of both lines were analyzed by G-banding and fluorescence in situ hybridization techniques. Both lines were composed of two cell subpopulations, a diploid population, which was found mainly in the MB49 line, and the tetraploid population, which was found mainly in the MB49-I line. A translocation between chromosomes 5 and 9 and an isochromosome of chromosome 19 were observed in the subpopulations of both lines. New structural abnormalities and additional chromosomal imbalances were detected in the MB49-I line. Tumor progression in the MB49/MB49-I model was associated with a selection of polyploid cells with accompanying chromosomal abnormalities. This model may be advantageous for the study of the genetic changes associated with the progression of bladder cancer.